Gender imbalances and labor market outcomes: Evidence from large-scale Mexican migration - Emily Conover; Melanie Khamis; Sarah Pearlman (IZA Journal of Development and Migration, 2021)
We study the consequences of international migration on labor market outcomes in a developing country. Specifically, we look at the case of Mexico, where large-scale international migration has led to significant declines in the male/female ratio. We explore whether this results in Mexican women entering high-skilled and better paying jobs over time. This question is relevant since there has been an increase in women's education and labor force participation across the developing world, but less evidence of improvements in the gender wage gap. Using an instrumental variables strategy that relies on historical migration patterns, we find that when there are relatively fewer men, women are more likely to work, have high-skilled jobs, and some earn higher wages. These results are robust to the inclusion of state, age group, and year fixed effects, and to different measures of migration and data sources. We explore investments in human capital as a key mechanism. We find that the gains in schooling are concentrated among women with the same average level of education of the men who migrate. From an aggregate perspective, these improvements in job type and wages are important given that higher female income may benefit the status, education, and health of both women and children, which in turn increases a country's development and growth. Our findings are among the few that show some movement toward improvements in the gender wage gap in a developing country setting.
Keywords: J21; J16; J31; O15; 330; gender wage gap; female labor force participation; sex ratio; Mexico; migration